Pressures of the E-Learning Practice in Light of The Spread of Corona Virus in Iraq a Case Study on Faculty in a Number of Iraqi Universities - Iman Amer Aldahhan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2025)
The study aimed to explore the phenomenon of functional pressure in e-learning and identify the primary challenges faced by university professors in e-learning during the Iraqi corona pandemic. The study adopted a descriptive analysis approach, and researchers employed targeted sampling techniques to contact a number of Iraqi universities in Baghdad. A total of 1,499 university faculties were approached, and 26 items were distributed online through social media platforms. Participants responded to the questionnaire. Data collection took place during the lockdown period in Iraq, spanning from May to September 2020. The findings from the comprehensive survey revealed that teachers across various academic degrees, genders, and years of service experience work pressure in e-learning. Notably, individuals with a PhD degree were found to face the highest levels of work pressure, particularly those holding the professor title. Keywords: E-learning, COVID-19, online teaching challenges, pandemic impact; educational technology